2020
DOI: 10.1093/nar/gkaa387
|View full text |Cite
|
Sign up to set email alerts
|

Structure of two G-quadruplexes in equilibrium in the KRAS promoter

Abstract: KRAS is one of the most mutated oncogenes and still considered an undruggable target. An alternative strategy would consist in targeting its gene rather than the protein, specifically the formation of G-quadruplexes (G4) in its promoter. G4 are secondary structures implicated in biological processes, which can be formed among G-rich DNA (or RNA) sequences. Here we have studied the major conformations of the commonly known KRAS 32R, or simply 32R, a 32 residue sequence within the KRAS Nuclease Hypersensitive El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 53 publications
2
47
0
Order By: Relevance
“…The CD melting curves were fitted with a two-states model by the van ’t Hoff analysis, and the melting temperatures along with the enthalpy changes obtained are collected in Table 1 . The T m values found for KRAS 32R and KRAS 22RT are in perfect agreement with those previously reported by Salgado et al (59.9 and 51.8 °C, respectively) in similar solution conditions (20 mM KH 2 PO 4 /K 2 HPO 4 , 60 mM KCl and 0.1 mM EDTA) [ 15 , 17 ]. Three-dimensional melting curves for G4s were also obtained by recording whole CD spectra as a function of temperature ( Figure S2 ).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The CD melting curves were fitted with a two-states model by the van ’t Hoff analysis, and the melting temperatures along with the enthalpy changes obtained are collected in Table 1 . The T m values found for KRAS 32R and KRAS 22RT are in perfect agreement with those previously reported by Salgado et al (59.9 and 51.8 °C, respectively) in similar solution conditions (20 mM KH 2 PO 4 /K 2 HPO 4 , 60 mM KCl and 0.1 mM EDTA) [ 15 , 17 ]. Three-dimensional melting curves for G4s were also obtained by recording whole CD spectra as a function of temperature ( Figure S2 ).…”
Section: Resultssupporting
confidence: 91%
“…Therefore, based on the recent NMR studies demonstrating that KRAS 32R adopts two major conformations in equilibrium with each other [ 17 ], a thermodynamic model was developed for a best fitting of the DSC profile (see the Materials and Methods Section for details), considering the following equilibria: Q1 ⇆ U Q2 ⇆ U where Q1 and Q2 are the two folded G4s, and U is the common unfolded DNA conformation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DMS footprinting experiments showed that G4 32R forms a parallel tri-stacked G4 with a 1/1/12 topology, characterized by two 1-nt loops, a 12-nt loop and a T-bulge in one strand ( Supplementary Information S3 ) [ 11 ]. A recent NMR study confirmed this structure, but showed that it is in equilibrium with a conformer containing a 11-nt loop, a folded-back guanine and 3-nt cap at the 3′-end [ 30 ]. By contrast, G4 mid comprising seven G-runs of at least three guanines can fold in different ways.…”
Section: Resultsmentioning
confidence: 96%